2016
DOI: 10.1016/j.btre.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of silver nanoparticle and its application in cell wall disruption to release carbohydrate and lipid from C. vulgaris for biofuel production

Abstract: HighlightsThe AgNP was successfully synthesised from soil isolated bacterium Bacillus subtilis.The synthesised AgNPs were confirmed by UV-Spec, FTIR, TEM and XRD.The AgNPs were successfully treated microalga to disrupt its cell wall to release lipids and carbohydrates.The cell wall damages evidenced by LDH assay and SEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…The AgNPs formation from silver nitrate solution incubated with P. aeruginosa supernatant overnight at 35°C was demonstrated by the color change of the reaction mixture to brown. The UV-Vis spectrometry exhibited the maximum absorption of the AgNPs at 455 nm Figure 1(a), which was consistent with the recorded range at 400-475 nm of AgNPs synthesized by various bioreductant such as bacterial supernatant (Abo-State & Partila, 2015Razack et al, 2016;Abo-State et al, 2017;Hussein et al, 2020a), fungal filtrates (Gudikandula et al, 2017), algal extracts (Abdel-Raouf et al, 2017;Arévalo-Gallegos et al, 2018) or plant extracts (Tripathi et al, 2017;Tahir et al, 2018;Ahmad et al, 2020). The AFM image suggested the spherical shape of the AgNPs with a size range of 6-12 nm, monodispersed Figure 1(b).…”
Section: Biosynthesis and Characterizations Of Agnpssupporting
confidence: 82%
See 4 more Smart Citations
“…The AgNPs formation from silver nitrate solution incubated with P. aeruginosa supernatant overnight at 35°C was demonstrated by the color change of the reaction mixture to brown. The UV-Vis spectrometry exhibited the maximum absorption of the AgNPs at 455 nm Figure 1(a), which was consistent with the recorded range at 400-475 nm of AgNPs synthesized by various bioreductant such as bacterial supernatant (Abo-State & Partila, 2015Razack et al, 2016;Abo-State et al, 2017;Hussein et al, 2020a), fungal filtrates (Gudikandula et al, 2017), algal extracts (Abdel-Raouf et al, 2017;Arévalo-Gallegos et al, 2018) or plant extracts (Tripathi et al, 2017;Tahir et al, 2018;Ahmad et al, 2020). The AFM image suggested the spherical shape of the AgNPs with a size range of 6-12 nm, monodispersed Figure 1(b).…”
Section: Biosynthesis and Characterizations Of Agnpssupporting
confidence: 82%
“…In a study on the effect of carbon, ferric oxide, and magnesium oxide NPs on the green alga Scenedesmus obliquus, it is suggested that the algal metabolism modifies its normal pathways toward, in most cases, lipid production (M. He et al, 2017). The AgNPs may break open the cell wall of C. vulgaris for the excretion of biomolecules such as proteins or lipids for biodiesel production (Razack et al, 2016). Table 4 shows the lipid profile of C. vulgaris and D. splendida before and after AgNPs treatment.…”
Section: Effects Of Agnps On Lipids and Carbohydratesmentioning
confidence: 99%
See 3 more Smart Citations